Prevalence of and factors associated with diarrhoeal diseases among children under five in Malaysia: a cross-sectional study 2016 - Aziz, Fazly Azry Abdul (BMC Public Health, 2018)
BACKGROUND: Globally, diarrhoea is one of the major causes of morbidity and mortality among children under than 5 years of age. There is a scarcity of published data on acute gastroenteritis (AGE) prevalence in Malaysia among children. This study aims to determine factors associated with diarrhoea in children aged less than 5 years in Malaysia. METHOD: Data from the National Health and Morbidity Survey 2016 conducted by Ministry of Health was analysed. This nationwide survey involved 15,188 children below five years old. The survey was carried out using a two-stage stratified sampling design to ensure national representativeness. The Questionnaire from UNICEF’s Multiple Indicator Cluster Survey (MCIS) was adapted to suit local requirements. Analysis was done using SPSS Version 23. Descriptive followed by multiple logistic regression were done to identify relevant factors. RESULT: The prevalence of diarrhoea among children under five in Malaysia was 4.4% (95% CI: 3.8,5.2). Analysis using logistic regression indicated that only ethnicity and usage of untreated water were significantly associated with diarrhoea among children after controlling for relevant factors. By ethnicity, children in the ‘Other Bumiputera’ group had 2.5 times the odds of having diarrhoea compared to children of Malay ethnicity. Children of Indian ethnicity were also at higher risk, at almost double the odds, as well as other ethnic groups (1.5 times). Children who used untreated water supply were two times more likely to develop diarrhoea. CONCLUSION: There is a higher risk of diarrhoea among children of ‘Other Bumiputera’ ethnicity, Indian ethnicities, and other ethnic groups and those who consume untreated water. Strategies to reduce diarrhoea among children should be targeted towards these at-risk populations. In addition, the Government must strive to ensure universal access to treated clean water in Malaysia and the Ministry of Health must focus on raising awareness on how to prevent diarrhoea.